Steerable Augmented Reality with the Beamatron - Wilson, Andy; Benko, Hrvoje; Izadi, Shahram; Hilliges, Otmar (UIST '12 Proceedings of the 25th annual ACM symposium on User interface software and technology, 2012)
Steerable displays use a motorized platform to orient a projector to display graphics at any point in the room. Often a camera is included to recognize markers and other objects, as well as user gestures in the display volume. Such systems can be used to superimpose graphics onto the real world, and so are useful in a number of augmented reality and ubiquitous computing scenarios. We contribute the Beamatron, which advances steerable displays by drawing on recent progress in depth camera-based interactions. The Beamatron consists of a computer-controlled pan and tilt platform on which is mounted a projector and Microsoft Kinect sensor. While much previous work with steerable displays deals primarily with projecting corrected graphics onto a discrete set of static planes, we describe computational techniques that enable reasoning in 3D using live depth data. We show two example applications that are enabled by the unique capabilities of the Beamatron: an augmented reality game in which a player can drive a virtual toy car around a room, and a ubiquitous computing demo that uses speech and gesture to move projected graphics throughout the room.